A portable electrochemical immunosensor for detection of S. aureus based on polyelectrolyte-modified screen-printed carbon electrode - Aleksei A. Evdokimov; Anna A. Baldina; Anna A. Nikitina; Timur A. Aliev; Artemii M. Zenkin; Mikhail V. Zhukov; Igor S. Pantyukhin; Ekaterina V. Skorb; Anton A. Muravev (Sensing and Bio-Sensing Research)
In this report, we present electrochemical immunosensors for the detection of S. aureus bacteria on the basis of SPCE/PEI/АBSA/PSS layer-by-layer assembly as a recognition element. QCM measurements and AFM imaging ensure effective adhesion of S. aureus antibody to PEI surface and its strong interactions with analyte through the PSS polyelectrolyte layer. Impedimetric detection of S. aureus gives the LOD of 1000 CFU/mL and the linear range from 104 to 107 CFU/mL and features facile assembly of recognition element and easy sampling. Voltammetric detection of the formation of the sandwich immunocomplex with secondary antibody in the outermost layer (AB–AG–AB-HRP) not only decreases the detection limit to 230 CFU/mL and expands the linear range of detection to 103–108 CFU/mL, but also could detect S. aureus bacteria with a portable open-source custom potentiostat in voltammetric mode, which is promising for non-invasive point-of-care monitoring of pathogens and addresses issues of antibody-based sensors, such as high cost and difficult chemical modification.